Prevalence of Intestinal Parasitic Infestations Among Children - Muhammad Khalid Javaid, Noureen Latif, Ali Nasre Alam (Journal of Rawalpindi Medical College, 2016)
Background: To find out the prevalence of parasitic infestation amongst children. Methods: A total of 1624 stool samples were collected for examination of prevalence of different helminths from the patients complaining for different GIT problems. Heliminths for which tests were performed included Hymenolepis nana, Giardia lamblia, Entamoeba histolytica , Enterobius vermicularis, Ascaris lumbricoides, Hook worm and Taenia . Each sample was screened depending upon the shape and morphology of the eggs and larvae of different helminths under microscope. Results:Out of 1624, 280 (17.24%) stools for positive for parasitic infestation. H. nana was the commonest found parasite. Majority presented in age group 4-6 years. Mean age of the respondents was 5±2.8 years Conclusions: Hymenolepis nana infection was observed in 6.0% respondents visiting Holy Family Hospital majority of the respondent were in early school going age.